Attitudes and Experiences Related to Feeding in Early Infancy in Guinea-Bissau. (29th May 2020) - Park, Mijung; Roberts, Susan; Laleau, Victoria; Rait, Michelle; Sa, Augusto Braima De; Flaherman, Valerie
Abstract: Objectives: Globally, more than 200 million children under 5 experience wasting and stunting. Wasting and stunting often begin during early infancy and have detrimental impacts on childhood health. Understanding local perspectives on feeding during early infancy might allow the design of interventions to improve early infant growth. The purpose of this study was to identify attitudes and experiences related to feeding during the first month after birth in Guinea-Bissau. Methods: We employed a mixed-methods approach to data collection, using focus groups and individual interviews. We completed five focus groups with mothers, fathers, community health workers and nurses, and six individual interviews with hospital administrators and policy makers. Portuguese and Mandinka, common languages in Guinea-Bissau, were used for data collection. All focus groups and interviews were recorded, translated and transcribed in English for analyses. Thematic analyses were used to examine variations in the participants' perspectives on a priori themes and to discern emerging themes. Results: A priori themes were (1) perspectives on breastfeeding, (2) issues related to infant health, (3) local practices of early supplementation, and (4) opinions about a nutritional intervention for infants. Emerging themes included (a) maternal health and (b) maternal supplementation. Participants reported a wide variety of feeding practices in early infancy, including exclusive breastfeeding, supplementation with baby formula and supplementation with other foods including fruit, grain, nuts, milk and herbs. Poverty, inadequate knowledge on breastfeeding and childhood health, and poor access to health care were identified as potential challenges for successfully implementing an intervention to improve growth during early infancy. Also, participants described that maternal health is fundamental to infant health and advocated for interventions supplementing mothers' nutrition. Conclusions: A wide range of feeding practices are common during the newborn period in Guinea-Bissau. While early interventions to improve infant growth may be acceptable and feasible, developing effective strategies must include components addressing the stakeholders' concerns related to poverty, inadequate knowledge and poor access to health care. Funding Sources: Melinda and Bill Gates Foundation.